Encyclopedia of American film serials - Mayer, Geoff (McFarland, 2017)
"From their heyday in the 1910s to their lingering demise in the 1950s, American film serials delivered excitement in weekly installments for millions of moviegoers, despite minuscule budgets, impossibly tight shooting schedules and the disdain of critics. This book analyzes four decades of productions from Pathé, Universal, Mascot and Columbia, along with all 66 Republic serials"--